The spectrum of the most common BRCA1/BRCA2 mutations in Lithuanian high risk families - Serapinas, Danielius; Sukys, Marius; Bartkeviciute, Agne; Barkauskiene, Diana; Bartkeviciene, Daiva (Genetika (Beograd), 2017)
Breast cancer is the neoplasm with the highest incidence and mortality among women in Lithuania. The aim of the study was to determine the mutational incidence in BRCA1 and BRCA2 genes in high-risk breast and/or ovarian cancer families. After written informed consent, 36 participants from Lithuanian health science university hospital provided a blood sample for genetic analysis. Molecular diagnostics was done for 6 BRCA1and BRCA2 mutations. From 36 tested subjects for BRCA1/BRCA2 mutations. Positive test for BRCA1/BRCA2 mutations test was found in 12 (33%) cases. Most common BRCA1 mutation was 5328insC - 6 (50%) cases, other mutations: 185delAG - 1 (8,3%), 300t>6(c61G) - 4 (33,3%), 4153 del A - 1 (8,3%). All mutations were BRCA1, but none of the women were positive for the analyzed BRCA2 mutation. The mean age when the cancer was diagnosed in BRCA1 mutations group was 40.40?3.39 comparing with the group without mutations - 43.29 ?2.52. Rates of BRCA1 and BRCA2 mutation testing are increasing in young women with breast and ovarian cancer. Detected mutations in BRCA1 contribute to up to one-third of the families with breast and ovarian cancer in Lithuania. nema